Implementasi Business Model Canvas (BMC) dalam Perencanaan Strategi Pemasaran Kewirausahaan UMKM (Studi pada “Citra Oleh-Oleh Lampung” di Bandar Lampung) - Daud, Syahril; Al Affan, Dhalvi; Rachman, Muhammad Farel; Al Fiqih, Muhammad Rizvy (Jurnal EMT KITA, 2025)
This study aims to apply the Business Model Canvas (BMC) as a strategic tool in designing marketing strategies to increase the competitiveness and sales of Toko Citra Oleh-Oleh Lampung, an MSME engaged in the field of regional souvenirs. The research method used is descriptive qualitative, with data collection through in-depth interviews, direct observation, and literature studies. Data analysis uses a thematic approach supported by SWOT analysis to identify strengths, weaknesses, opportunities, and threats in the business. The results of the study show that the main elements in the BMC, such as Customer Segments, Value Propositions, and Channels, play a significant role in determining an effective marketing strategy. Lampung's typical products with local cultural values, distributed through physical and digital stores, and a focus on customer experience are the main advantages. However, the study also identified challenges, such as dependence on tourists and logistical constraints, which need to be addressed through product diversification, digital marketing optimization, and operational efficiency. This study provides a practical contribution to Toko Citra Oleh-Oleh Lampung in increasing its competitiveness in the local and national markets. In addition, the results of this study are expected to be a reference for other MSMEs in facing competition in the era of globalization. Suggestions for further research are to conduct a comparative study between MSMEs that implement BMC and those that do not, to show the effectiveness of this strategy in more depth.